Vertically Distributed Sensing of Deformation Using Fiber Optic Sensing - Zhang, Cheng‐Cheng; Shi, Bin; Gu, Kai; Liu, Su‐Ping; Wu, Jing‐Hong; Zhang, Song; Zhang, Lei; Jiang, Hong‐Tao; Wei, Guang‐Qing (Geophysical research letters, 2018)
Vertical deformation can be revealed by various techniques such as precise leveling, satellite imagery, and extensometry. Despite considerable effort, recording detailed subsurface deformation using traditional extensometers remains challenging when attempting to detect localized deformation. Here we introduce distributed fiber optic sensing based on Brillouin scattering as a geophysical exploration method for imaging distributed profiles of vertical deformation. By examining fiber optic cable‐soil interaction we found a threshold in confining pressure to achieve a strong cable‐soil coupling, thus validating data collected from a borehole‐embedded fiber optic cable deployed in Shengze, southern Yangtze Delta, China. Clear‐cut strain profiles acquired from November 2014 to December 2016 allowed us to pinpoint where compaction or rebound was actively occurring and examine strain responses at various locations along the entire cable length. We suggest that distributed fiber optic sensing can complement with extensometry and remote sensing techniques for improved monitoring of vertical deformation. Plain Language Summary Recording detailed subsurface deformation using traditional methods (e.g., extensometers) is sometimes difficult due to limited measuring points. This dilemma may be overcome by using the emerging distributed fiber optic sensing technology, which transforms common telecommunication fiber optic cables into sensors capable of making distributed strain measurements. We report the use of this technology for monitoring distributions of vertical deformation resulting from groundwater ion in Shengze, southern Yangtze Delta, China. An evaluation of the performance of a borehole‐embedded fiber optic cable helps us to validate the in situ strain data. The advantage of using this technology for vertical deformation sensing is the ability to locate any strata undergoing compaction or rebound and look at strain responses at any depth of interest. Moreover, recording subsurface changes in this fashion may also be useful in other geophysical and engineering applications that require refined monitoring of the media. Key Points Distributed fiber optic sensing with Brillouin scattering provides a clear subsurface strain profile using a single fiber optic cable We find a threshold in confining pressure to achieve a strong fiber optic cable‐soil coupling Distributed fiber optic sensing can complement with existing techniques for improved monitoring of vertical deformation